Enhanced air quality prediction using adaptive residual Bi-LSTM with pyramid dilation and optimal weighted feature selection - R. Sudha; Ajith Damodaran; Gunaselvi Manohar (Scientific Reports)
Abstract In most industrial and urban regions, monitoring and safeguarding the air’s purity is considered one of the most crucial tasks for government agencies. In numerous industrial and urban locations, preserving and tracking the condition of the air has become the primary concern. However, implementing comprehensive air quality monitoring systems often requires significant financial investment. The performance of current air quality monitoring sensors declines over time, which leads to inaccurate measurements of air pollution levels. To address this challenge, it is essential to develop and implement strategies aimed at maintaining sensor accuracy and effectively resolving environmental issues related to air quality. To facilitate an effective air quality prediction and assessment, a deep learning network is proposed. At first, the data for predicting air quality are collected from the relevant data sources. The proposed model introduces a novel methodology for weighted feature selection utilizing an Improved Gannet Optimization Algorithm (IGOA) aimed at enhancing the performance of data classification. After extracting the weighted features, classification is carried out using an Adaptive Residual Bi-LSTM network combined with Pyramid Dilation (ARBi-LSTM-PD), which significantly increase the model’s potential to identify complex patterns within the data. The efficacy of the implemented model is enhanced by optimizing the parameters from RBi-LSTM using the IGOA strategy. This approach tackles the difficulties associated with feature selection and classification, leading to distinct advancements in the quality of the classification results. The robustness of the model is examined and analyzed using different measures. The accuracy and precision rate of the proposed model are 95.175% and 87.2%, which is better than traditional air quality prediction models. Thus, the simulation results demonstrate that it obtains the desired results for predicting and assessing the quality of air.